Establishment and Genetic Landscape of Precancer Cell Model Systems from the Head and Neck Mucosal Lining - de Boer, D Vicky; Brink, Arjen; Buijze, Marijke; Stigter-van Walsum, Marijke; Hunter, Keith D; Ylstra, Bauke; Bloemena, Elisabeth; Leemans, C René; Brakenhoff, Ruud H (Molecular cancer research, 2019)
Head and neck squamous cell carcinomas (HNSCC) develop in fields of genetically altered cells. These fields are often dysplastic and a subset can be recognized as (erythro)leukoplakia, but most are macroscopically invisible. There is a lack of adequate treatment options to eradicate these fields, whereas they underlie the development of primary tumors as well as part of the local relapses. Unfortunately, there are almost no representative cellular models available to identify suitable treatment options. To this end, clinical biopsy specimens ( = 98) were cultured from normal appearing mucosa of the surgical margins of patients with primary HNSCCs ( = 32) to generate precancer cell culture models. This collection was extended with six previously established precancer cell cultures. Genetic analysis was performed on cultures with an extended life span (≥20 population doublings), the previously established cultures, and some randomly selected cultures. In total, cancer-associated changes were detected in 18 out of 34 (53%) cultures analyzed, which appeared to be independent of life span. A variety of genetic changes were identified, including somatic mutations as well as chromosomal copy-number aberrations (CNA). Loss of /p16 and mutations in /p53 were most prominent. Remarkably, in some of these precancer cell cultures only chromosomal CNAs were detected, and none of the frequently occurring driver mutations. IMPLICATIONS: The precancer cell cultures, characterized herein, form a representative collection of field models that can be exploited to identify and validate new therapeutic strategies to prevent primary HNSCCs and local relapses.